Structural geology of rocks and regions - Davis, George H. (George Herbert), 1942-; Reynolds, Stephen J.; Kluth, Chuck (Wiley, 2012)
"Relates the physical and geometric elegance of geologic structures within the Earth's crust and the ways in which these structures reflect the nature and origin of crystal deformation through time. The main thrust is on applications in regional tectonics, exploration geology, active tectonics and geohydrology. Techniques, experiments, and calculations are described in detail, with the purpose of offering active participation and discovery through laboratory and field work"--